Study Of Lemang Kancung Beruk At Dusun Baru Lempur Village Kerinci Regency - JR, Mutiara; Fridayati, Lucy (Jurnal Pendidikan Tata Boga dan Teknologi, 2022)
This research to learn and gain deeper knowledge about lemang kancung beruk at Dusun Baru Lempur village, Kerinci Regency. This Lemang is liked by the public because of its different taste and unique shape where the packaging is wrapped in a kantong semar(nepenthes). The purpose of this study was to identify materials, equipment, study processing techniques, describe variants and utility of lemang kancung beruk at  Dusun Baru Lempur village. This type of research is qualitative research. The research data were obtained from local community women who are experts in making lemang kancung beruk at traditional events and local community women who are proficient and have made lemang kancung beruk for various events. Data analysis that is data reduction, data presentation, conclusions and verification. The results of the study concluded that the ingredients used included white glutinous rice, black sticky rice, red sticky rice, coconut milk, salt and kantong semar(nepenthes). The tools used are a small bowl, large bowl, spoon, steamer and gas stove. The processing technique are use steaming.